NANOSTRUCTURED UNSATURATED POLYESTER USING BLOCK COPOLYMERS: MORPHOLOGY, OPTICAL PROPERTIES AND FRACTURE TOUGHNESS RELATIONSHIP - Hernández, Hugo; Hernández-Ortiz, Juan P.; Cano, Laida; Mondragon, Iñaki; Tercjak, Agnieszka; Builes, Daniel H. (Revista Colombiana de Materiales, 2014)
Novel nanostructured unsaturated polyester thermosets modified with two poly(ethylene oxide-b-propylene oxide-b-ethylene oxide) block copolymers, were developed. Effects of molecular weights and blocks ratio on optical and mechanical properties were reported. It was found that self-assembly or polymerization-induced phase separation mechanisms were followed by the nanostructured thermosetting systems to achieve the final morphology. Relationships between final morphology and optical and mechanical properties of thermosets were examined.